Metodología para el desarrollo de la rapidez de reacción y su incidencia en la efectividad de los arqueros de fútbol de la categoría sub 12 de la liga deportiva cantonal de Baba - Cueva Vite, Kerlly Tatiana (2016)
In this research the analysis of how influences methodology for the development of rapid reaction in the effectiveness of the goalkeepers of the Under 12 Liga Deportiva Cantonal de Baba collecting data through surveys coaches held and guide observation addressed to the gatekeepers determining what is the impact of the methodology for the development of rapid reaction in the effectiveness of the goalkeepers of the Under 12 Liga Deportiva Cantonal de Baba. Also emphasizing the need for strategies as a means to achieve the objectives and have success on the sports field. It was determined that the methodology used to develop the reaction rate has no influence on the air, distribution of equipment and saves archers soccer sub 12 category Liga Deportiva Cantonal de Baba. The present study was performed in order to Prepare a training guide for the development of rapid reaction in the effectiveness of the archers of football in order to improve the methodology used by goalkeeper coaches. Therefore football archers will respond positively and will be satisfied as all your needs will be solved this will allow them to improve the methodological knowledge of soccer coaches in the Liga Deportiva Cantonal de Baba